Disseminated intravascular coagulation - Suhardi DA Suhardi DA (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
Bleeding may result from abnormalities' of platelet, blood vessel walls, or coagulation. Acquired deficiency of coagulation factors is usually the result of impaired production or increased extravascular loss. Inappropriate intravascular utilization of coagulation factors, which is usually prevented by continuous rapid blood flow, circulating inhibitors of procoagulants, and removal of activated clotting factors, may result as defibrinogenation syndrome, disseminated intravascular coagulation, or consumption coag-ulopathy. Factors responsible for the diseminared intravascular coagulation include release of thromboplastic material into the circulation, endothelial damage, endotoxemia, antigen-antibody reactions, hypertension, hypoxia, acidosis, and re uculoendothelial blockage.This paper describes the clinical manifestations, pathogenesis and management of the disseminated intravascular coagulation which might be not so rare in the clinics.Key Words: disseminated in travascularcoagulation -hemon-hage.-defibrinogenation syndrome - coagulopathy -procoagulant inhibitor